Роль тиреотропного гормону у генезі раку щитоподібної залози - Черненко, О. В.; Хоперія, В. Г. (Clinical Endocrinology and Endocrine Surgery, 2013)
There is mounting evidence that the serum concentration of TSH is an independent predictor for the diagnosis of thyroid malignancy in patients with nodular thyroid disease. Furthermore, preoperative serum TSH concentrations are higher in patients with more aggressive tumors, suggesting a potential role for TSH in the progression of differentiated thyroid cancer. Based on these observations, patients with higher serum TSH concentrations and borderline cytological results may require more aggressive investigation and treatment when compared with those with lower baseline TSH levels. The mechanisms underlying the finding of higher serum TSH in patients with thyroid cancer remain unexplained. According to the analysis of the relationship of TSH and frequency of papillary thyroid cancer, found significantly increased levels of TSH in patients with thyroid cancer compared with benign tumors. They found significantly higher TSH concentrations in patients who were subsequently diagnosed with thyroid cancer compared with those with benign disease. In addition, they found that the development of autonomous thyroid function (TSH<0.4 mU/ml) was associated with a reduction in the risk of papillary thyroid carcinoma. In this review we present evidence for an association between TSH and thyroid cancer.